Pengembangan E-Modul Laju Reaksi Berbasis Discovery Learning untuk Kelas XI SMA/MA - Lendra, Nova (RC-INSTITUT, 2019)
The learning process in the 2013 curriculum refers to the scientific approach using discovery leanning models. The purpose of this study is to develop e-module based on discovery learning in the reaction rate material for science of class XI SMA/MA and determine the level of validity and practicality of the e-module developed. The type of research conducted is research and development (R&D) with a 4-D development model. The e-module which is carried out is validity test and practicality test. Validity test is carried out by 2 chemistry lecturers at FMIPA UNP, 3 chemistry teachers (chemistry teacher at SMAN 1 Hiliran Gumanti, chemistry teacher at SMAN 1 Payung Sekaki, chemistry teacher at SMAN 1 Danau Kembar). While the practicality test was carried out by 3 chemistry teachers and 19 students for class XI of Science at SMAN 1 Hiliran Gumanti 2018/2019 academic year. The research instrument used was a validity questionnaire and practical questionnaire whose results would be analyzed using the Cohen Kappa formula. This study produces e-module based on discovery learning in the reaction rate material with a mean moment of kappa 0.89 with a very high validity level. The results of the teacher practicality test and the practicality test of the students were obtained by means of sequential kappa moments of 0.90 and 0.87 with a very high degree of practicality.